Parenteral Methotrexate Is Efficient in the Treatment of Azathioprine Refractory Crohn’s Disease - Gökbulut, Volkan; Özin, Yasemin; Kalkan, İsmail Hakkı and Arı, Derya and Yüksel, Mahmut and Yalın Kılıç, Zeki Mesut and Kayaçetin, Ertuğrul (Turkish Journal of Gastroenterology, 2022)
Background: There is limited data in the literature analyzing the efficacy of methotrexate in Crohn’s disease used after thiopurine analogs. We aimed in our study to show the efficacy of methotrexate in Crohn’s disease patients who failed to respond to thiopurine treatment. Methods: The study included 29 azathioprine refractory patients with Crohn’s disease. Intramuscular methotrexate (25 mg/week) in the induction of remission and intramuscular methotrexate (15 mg/week) in 29 CD patients with a median follow-up time of 13 months was performed. In 15 (51.7%) patients, methotrexate was used in combination with anti-Tumour necrosis factor (TNF) (combination group), while it was used in 14 (48.3%) patients in monotherapy (monotherapy group). Results: The mean Harvey–Bradshaw index score significantly decreased in the follow-up period (Wk0 = 7.6, last visit = 4.5, P < .001). Remission and response rates at week 12 were 75.9% and 79.3%, respectively. Maintenance of remission (77.8% vs 37.5%, respectively, P = .1) and response rates (77.8% vs 50%, respectively, P = .3) due to last visit examination were numerically higher in combination group but they were not statistically significant. The cumulative probability of remission maintenance in patients with methotrexate therapy was 72.7%, 33.1%, and 22.0% at 1, 2 ,and 4 years after starting methotrexate, respectively. Conclusion: Our results show that parenteral use of methotrexate is efficacious in inducing and maintaining remission as a step-up agent in azathioprine refractory Crohn’s disease patients Cite this article as: Gökbulut V, Özin Y, Kalkan İH, et al. Parenteral methotrexate is efficient in the treatment of azathioprine refractory Crohn’s disease. Turk J Gastroenterol. 2022;33(2):111-118.